[O iii] Emission line properties in a new sample of heavily reddened quasars at z > 2. Issue 2 (23rd May 2019) - Temple, Matthew J; Banerji, Manda; Hewett, Paul C; Coatman, Liam; Maddox, Natasha; Peroux, Celine
ABSTRACT: We present VLT-SINFONI near infra-red spectra of 26 new heavily reddened quasar candidates selected from the UKIDSS-LAS, VISTA VHS, and VIKING imaging surveys. This new sample extends our reddened quasar search to both brighter and fainter luminosities. 25 of the 26 candidates are confirmed to be broad line quasars with redshifts 0.7 < z < 2.6 and dust extinctions 0.5 < E ( B − V ) < 3.0. Combining with previously identified samples, we study the H α, H β, and [O iii ] emission line properties in 22 heavily reddened quasars with L bol ≈ 10 47  erg s −1 and z > 2. We present the first comparison of the [O iii ] line properties in high luminosity reddened quasars to a large sample of 111 unobscured quasars in the same luminosity and redshift range. Broad wings extending to velocities of 2500 km s −1 are seen in the [O iii ] emission line profiles of our reddened quasars, suggesting that strong outflows are affecting the ionized gas kinematics. However, we find no significant difference between the kinematics of the [O iii ] emission in reddened and unobscured quasars when the two samples are matched in luminosity and redshift. Our results are consistent with a model where quasar-driven outflows persist for some time after the obscuring dust has been cleared from along the line of sight. Assuming the amount of ionized gas in reddened and unobscured quasars is similar, we use the equivalent width distribution of the [O iii ] emission to constrain the location of the obscuring dust in our reddened quasars. We find that the dust is most likely to be located on galactic scales, outside the [O iii ] emitting region.